Methodology for the preparation of the teacher of the Granma sports schools in the treatment of intangible cultural heritage as historical content (Original) (Revista científica Olimpia, 2020)
The neoliberal platform of thought carried out by US imperialism towards our country is aimed at breaking the traditions and historical roots of our people. That is why special attention has been paid to the teaching-learning of the subject History of Cuba in the formation of the bachelor who studies the Pre-university educational level in the system of sports schools that train athletes in the Upper Middle Level and particularly the need to incorporate cultural heritage studies as a way to position the country's future athletes in the contemporary world and commit them to be agents of the construction of the future. It is a prioritized task of the teacher who teaches the subject History of Cuba to guarantee the training of an athlete who feels identified with the cultural roots of the sociocultural context, for which reason this research aims to develop a methodology to contribute to the preparation of the teacher of sports schools in the Granma province in the didactic treatment of intangible cultural heritage as historical content, integrating the processes of student motivation, methodological construction, and the articulation of knowledge, leading to the transformation of their way of performance in the training of the bachelor graduated from the sports schools of the Granma province. To treat the problem in question, a diagnosis was made of 12 teachers from sports schools in the Granma province, which allowed taking the data obtained as a starting point for its development. The importance of the proposed methodology is its contribution to the improvement of the teacher who teaches the subject History of Cuba, and the achievement of a competent, creative graduate capable of acting in the sociocultural context where it takes place.
Keywords: metodología; patrimonio cultural inmaterial; contexto sociocultural; contenido histórico.